HUMAN-PLANT RELATIONSHIPS DURING THE COPPER AND BRONZE AGES IN THE BAZA AND GUADIX BASINS (GRANADA, SPAIN) - ARIZA, M O R (BULLETIN DE LA SOCIETE BOTANIQUE DE FRANCE-ACTUALITES BOTANIQUES, 1992)
The anthracological study of six sites in the north of province of Granada (Spain) has uncovered vegetation for the Copper Age formed by a dense oak grove belonging to the association Rhamno-Quercetum cocciferae. In the Bronze Age, the intensification of agriculture caused changes in the vegetation, reflected in the anthracological diagrams by the increase in Pinus halepensis and the decrease of Quercus ilex-coccifera, as well a decline in the woodlands and an expansion of the legumes. The different species present in the vicinity of the site (or in a greater radius), servings such specific functions as the making of tools and utensils, house construction, and firewood for the hearth or for fours, give us preliminary insights into the ways in which these populations used space and their vegetal environment
Keywords: CHARCOAL ANALYSIS; COPPER AGE; Granada; Spain